Introduction to No. 1, Part two: Developing Moral Competence, Perfecting Selfhood, Practicing Forgiveness - Bardziński, Filip (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
The introductioń to Ethics in Progress Special Issue, Vol. 7(1), No. 2 is given, with brief exposes on the articles present in the section.
Keywords: KMDD®; Paul Ricoeur; selfhood; moral and democratic competence; John Dewey